(untitled) (International Educators Conference, 2025)
The article identifies fakhr couplets within the ghazals of the Turkic poet Atoyi’s poetic divan, analyzing the literary devices, hidden meanings, and proverbs used in connection with these fakhr elements. This artistic device is examined through a classification into specific types.